Evaluation of genscript cpass and immusafe covid+ assays in detection of sars-cov-2 neutralising antibody titres in coronavac second and BNT162b2 booster doses - Izani, Wani Husna Mohd (2023)
Coronavirus disease 2019 (COVID-19) outbreak in 2020 was caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The pandemic has affected a lot of people worldwide, resulting in COVID-19 vaccines being developed as an effort to stop the pandemic. The vaccines approved by the Malaysian government include Sinovac CoronaVac and Pfizer-BioNTech BNT162b2. Vaccination can increase the level of neutralising antibodies and protect against COVID-19 infections. Neutralising antibodies are essential in monitoring the effectiveness of the vaccines against SARSCoV- 2. Several assays have been developed to detect neutralising antibody titres in individuals. The purpose of this study was to evaluate the two commercialized assays, GenScript cPass and ImmuSAFE COVID+ tests in detecting SARS-CoV-2 neutralising antibody titres. Both assays used a total of 26 serum samples of CoronaVac second (n = 13) and BNT162b2 booster (n = 13) doses. The study also determined neutralising antibody titres between males and females among young adults in second and booster doses. The results showed the titre of neutralising antibodies was higher in BNT162b2 booster dose than in CoronaVac second dose serum samples. The analysis of the demographic data showed neutralising antibody titres in females were higher than in males among young adults in second and booster dose samples. The study concluded that both assays were reliable in detecting neutralising antibodies in serum samples following vaccination.